LOST – AND GAINED – IN TRANSLATION: Kulturel oversættelse som transformativt rum - Gimpel, Denise; Thisted, Kirsten (Tidsskriftet Antropologi, 2007)
In the article we approach the topic of cultural encounter through the concept of cultural translation and argue – in line with postcolonial theorists like Homi Bhabha – that this concept is far more open to minority positions than the Danish concept of ‘kulturmøde’ (literally: the meeting of cultures), and that it brings into focus creativity, negotiation and transformation, rather than the usual debate about integration or assimilation. All societies undergo a constant process of cultural translation and any translation involves an aspect of violence, but it also opens up transgressing and transformative spaces, where ‘newness enters the world’. The aim of the article is to introduce the panorama of possibilities in which cultural translation may be understood and illustrate the breadth of application of the available analytical concepts. The empirical examples are taken from China and Greenland; structurally two very different situations, but sharing the fact that Western culture was seen as superior and therefore introduced by local intellectuals as a means to achieve equality and progress. However, as Orhan Pamuk has tried to illustrate in the novel Snow, a narrative of loss can be constructed as a result of resentment or fear at the sense of having been (culturally) translated into something alien. Pamuk’s novel points to the serious conflicts involved in the process of cultural translation. Transformation and manipulation, deduction from, and addition to, cultural heritage and identity are something quite more than merely an innocent ‘meeting’ of different cultures.